Analisis Penggantian Exhaust System terhadap Performance Engine type 2NR-VE - Ahmad Fahmi; Tatang Permana (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Engine performance is a critical parameter in automotive engineering as it directly affects power output, torque characteristics, and overall vehicle efficiency. One of the components that significantly influences engine performance is the exhaust system, which regulates exhaust gas flow and back pressure. This study aims to experimentally analyze the effect of replacing a standard exhaust system with an aftermarket exhaust system on the performance of a 2NR-VE engine. The research employed an experimental method using a comparative design with two testing conditions: a factory-standard exhaust system and an aftermarket exhaust system. Engine performance testing was conducted using a dynamometer (dyno test) to measure horsepower and torque across various engine speed ranges (RPM). Each testing condition was performed repeatedly, and the resulting data were averaged to reduce measurement errors and minimize the influence of operational fluctuations. The experimental results indicate that the aftermarket exhaust system significantly improves engine performance. The maximum power increased from 82.5 HP to 91.6 HP, while the maximum torque rose from 131.2 Nm to 154.4 Nm. These improvements suggest that the aftermarket exhaust configuration effectively reduces exhaust back pressure and enhances exhaust gas flow efficiency. Therefore, replacing the exhaust system can be considered an effective approach to improving engine performance, provided that the modification is technically appropriate and complies with applicable emission and noise regulations.